Reading Fluency of Higher Education Students - Ana Sucena; Cátia Marques; Ana Silva; João Falcão Carneiro (Paidéia (Ribeirão Preto), 2022)
Abstract The literature that links career development with reading skills is scarce. This study seeks to fill this gap, for which the reading fluency of college students was analyzed, taking into account the choice of more/less desirable courses. Desirability is based on the classifications for college access. 211 students participated in the study, 132 female, attending four courses: Mechanical Engineering, Health, Psychology, and Education, in three Portuguese Public Universities. The instruments used were the sociodemographic form and the Teste de Idade de Leitura (Reading Age Test - TIL). The results indicated that students attending less desirable courses (i.e., Education and Health) are significantly less fluent and; students who score lower on reading fluency are more likely to belong to the Education course. This study stresses the importance of the distribution of students by the different areas of studies should not reflect reading fluency asymmetries.